2014
DOI: 10.4274/tjod.82621
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thickened endometrium in tamoxifen therapy

Abstract: Objective:Aim of this study was to evaluate role of hysteroscopy in thickened endometrium (>5 mm) associated with tamoxifen therapy.Materials and Methods:We performed dilatation and curettage (D&C) and hysteroscopic biopsy to patients for evaluation of thickened endometrium in tamoxifen therapy. One hundred and nine asymptomatic patients with estrogen receptor positive breast cancer treated with tamoxifen 20 mg daily. We performed hysteroscopic biopsy or D&C to patients who have thickened endometrium at transv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Other risk variables, such as body mass index, length of treatment, and prior estrogen replacement therapy to avoid endometrial cancer while taking tamoxifen, were also considered. [3,4] Tamoxifen use for more than five years has been linked to an increased chance of endometrial cancer in previous research. The ATLAS study found that taking tamoxifen for more than five years decreased the chance of breast cancer recurrence but raised the risk of endometrial cancer.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other risk variables, such as body mass index, length of treatment, and prior estrogen replacement therapy to avoid endometrial cancer while taking tamoxifen, were also considered. [3,4] Tamoxifen use for more than five years has been linked to an increased chance of endometrial cancer in previous research. The ATLAS study found that taking tamoxifen for more than five years decreased the chance of breast cancer recurrence but raised the risk of endometrial cancer.…”
Section: Discussionmentioning
confidence: 97%
“…[1,2] There are no recommendations that suggest gynecological testing for endometrial cancer in premenopausal women taking tamoxifen. [3,4] In this article, we will look at a tamoxifen-treated breast cancer case to better understand one of the most serious consequences, endometrial cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen, for instance, though osteoprotective like estrogen (1,2), is reported to increase the uterine weight, endometrial cancer, stroke, and pulmonary embolism (3). A drug that has protective effects in estrogen-dependent tissues and prevents its deleterious effects would serve as an ideal SERM (4).…”
Section: Introductionmentioning
confidence: 99%
“…Tamoxifen and raloxifen are the most commonly used SERMs in treating breast cancer, which is often observed to exert side effects in hormone dependent-tissues. Tamoxifen, for instance, though osteoprotective like estrogen ( 1 , 2 ), is reported to increase the uterine weight, endometrial cancer, stroke, and pulmonary embolism ( 3 ). A drug that has protective effects in estrogen-dependent tissues and prevents its deleterious effects would serve as an ideal SERM ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is very important and vital to diagnose endometrial cancer before cardinal symptoms [especially postmenopausal bleeding] begin. Transvaginal ultrasonography [TVUS], which is used as part of a gynecological examination to view endometrial pathologies helps detect endometrial cancer and provides important information in the differential diagnosis of other endometrial pathologies in symptomatic postmenopausal patients [1,2]. Although the availability of TVUS as a screening method for endometrial or ovarian cancer is limited, TVUS is performed during routine gynecological examinations in asymptomatic postmenopausal women [3,4].…”
Section: Introductionmentioning
confidence: 99%